Retalho omnicanal : segmentação de clientes que compraram em lojas físicas após serem acionados por email marketing - Bassoli, Daniel Dias Galvão (2017)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence